Influence of the Connector Area on the Chipping Rate of the VM9 Veneering Ceramic in a Posterior Four-Unit Yttria-Stabilized Tetragonal Zirconia Polycrystal Fixed Dental Prostheses: A Pilot Study - Haddad, Camille; Meyer, Jean-Marc; El Ahmadié, Mayssaê (European Journal of General Dentistry, 2021)
Objective The purpose of this study was to evaluate the influence of the connector area on the chipping rate of the VM9 veneering ceramic in a 4-unit yttria-stabilized tetragonal zirconia polycrystal (Y-TZP) framework, using a novel sonographic technique.Materials and Methods The framework was designed as a 4-unit fixed dental prostheses (FDP) with two abutment teeth at the first mandibular premolar and second mandibular molar. The cross-sectional area of the connector was 7.5, 8, or 9 mm2. The prepared teeth were scanned using CAD/CAM technology, and five frameworks were prepared for each design, making a total of 15. The frameworks were divided according to the veneering ceramics: Y-TZP FDPs using Vita VM9 (12 frameworks), and porcelain fused to metal (PFM) FDPs using Vita VM13 (3 frameworks). The specimens were statically loaded until failure. To capture the initiation of the failure within the specimens, a novel sonographic technique, designed for this research, combining acoustic emission and visual monitoring during live load bearing tests, was used to determine the failure load value. Failed frameworks were inspected using a microscope, and failure patterns were identified. One-way ANOVA and Tukey HSD tests were applied for statistical analysis of the results (p-value ≤ 0.05).Results Despite the fact that the chipping strength is proportional to the cross-sectional area of the connector, the effect of the cross-sectional area on chipping load revealed no statistically significant differences, while PFMs showed superior chipping strength relative to the zirconia frameworks regardless of the connector's size. A high rate of catastrophic fracture occurred while loading the specimens.Conclusion The effect of the cross-sectional area on chipping load revealed no statistically significant differences in Y-TZP frameworks. The novel sonographic technique may be a potential method to study the behavior of dental ceramics, including chipping and fracture.
Keywords: chipping rate; connector area; four-unit fixed dental prosthesis; sonographic technique; static load bearing test